2018
DOI: 10.1128/jvi.00301-18
|View full text |Cite
|
Sign up to set email alerts
|

New Threats from H7N9 Influenza Virus: Spread and Evolution of High- and Low-Pathogenicity Variants with High Genomic Diversity in Wave Five

Abstract: H7N9 virus has caused five infection waves since it emerged in 2013. The highest number of human cases was seen in wave 5; however, the underlying reasons have not been thoroughly elucidated. In this study, the geographical distribution, phylogeny, and genetic evolution of 240 H7N9 viruses in wave 5, including 35 new isolates from patients and poultry in nine provinces, were comprehensively analyzed together with strains from first four waves. Geographical distribution analysis indicated that the newly emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 53 publications
3
107
0
Order By: Relevance
“…The fifth epidemic wave in 2016-2017 was the most severe with 759 confirmed human cases, probably due to the geographical spread of the virus from eastern China throughout the whole country [7]. More importantly, the H7N9 viruses isolated during the fifth epidemic wave have evolved into two distinct lineages, namely, the Yangtze River Delta and Pearl River Delta lineages [8][9][10]. Some of these fifth-epidemic-wave H7N9 isolates of Yangtze River Delta lineage carried polybasic amino acids at the HA1/HA2 cleavage site, a characteristic of highly pathogenic avian influenza viruses [11].…”
Section: Introductionmentioning
confidence: 99%
“…The fifth epidemic wave in 2016-2017 was the most severe with 759 confirmed human cases, probably due to the geographical spread of the virus from eastern China throughout the whole country [7]. More importantly, the H7N9 viruses isolated during the fifth epidemic wave have evolved into two distinct lineages, namely, the Yangtze River Delta and Pearl River Delta lineages [8][9][10]. Some of these fifth-epidemic-wave H7N9 isolates of Yangtze River Delta lineage carried polybasic amino acids at the HA1/HA2 cleavage site, a characteristic of highly pathogenic avian influenza viruses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on phylogenetic analysis of the HA gene, the zoonotic H7N9 AIVs have been classified into two main lineages, the Yangtze River Delta (YRD) and Pearl River Delta (PRD) lineages; the first H7N9 HPAIV was derived from the YRD lineage (D. Wang et al, ; Yang et al, ). Recent studies have shown that the YRD lineage was dominant in the distribution of zoonotic H7N9 AIVs in China (Qi et al, ; Quan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the internal genes of the HPAI H7N9 viruses were derived from H7N9/H9N2 viruses; however, the internal genes of these HPAI H7 viruses, including the human virus, have three sources, H7N9/H9N2 from poultry, H5N6, and the Eurasian wild‐bird gene pool (Figure C‐H). PB2, PB1, PA, and NS genes were derived from H7N9/H9N2 or the Eurasian wild‐bird gene pool, while the NP gene was from H7N9/H9N2 from poultry, H5N6, or the Eurasian wild‐bird gene pool.…”
Section: Resultsmentioning
confidence: 99%
“…The HPAI H7N9 virus might have emerged in mid‐2016, according to a molecular clock model . Frequent reassortments of internal genes among H7N9 and H9N2 viruses have been observed in the HPAI H7N9 viruses, similar to those in the LPAI H7N9 viruses . As of December 19, 2018, twenty‐seven outbreaks in poultry have been reported in 12 provinces in China, about 900 000 poultry have been culled (http://www.oie.int).…”
Section: Introductionmentioning
confidence: 99%